EVALUASI INOVASI PELAYANAN PUBLIK JAKWIR CETEM DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA TEGAL - Annisa Syafaatul Azmi; R Slamet Santoso; Retna Hanani (Journal of Public Policy and Management Review, 2022)
Public service innovation is a change in the implementation of services from offline to online by utilizing the sophistication of digital information which has now become a primary need. Therefore, many studies have been conducted on public service innovations in Disdukcapil, but generally only look at the user side so this study aims to analyze how far the success of the Tegal City Disdukcapil in implementing the "Jakwir Cetem" innovation more comprehensively and analyze the factors that support and hinder the implementation of the innovation. "Jakwir Cetem" is an innovation of the Tegal City administration document service provider in the form of an android application. This research uses the policy of Kepmenpan RB Number 50 of 2022 and theoretical studies from Irwin., et al and Albury. Descriptive qualitative research method with data collection approach through observation, interviews, and documentation. The results show that the innovation of "Jakwir Cetem" in general has met the five criteria for evaluating public service innovations contained in Kepmenpan-RB Number 50 of 2022. However, there are still people in Tegal City who have not felt the benefits, due to the influence of budget and planning factors that are lacking. managed properly so that there is no incentive for Adminduk Volunteers, and the factor of the lack of active support from local officials, namely the RT Chair in carrying out brand awareness of the "Jakwir Cetem" program. Recommendations to the people of Tegal it is time to leave the old submission method and switch to a new submission via online so that the value of the benefits of "Jakwir Cetem" can be accepted by all Tegal people, then the Disdukcapil of Tegal City is expected to be able to give something of value to Adminduk Volunteers and are expected to embrace RT devices village in order to ensure the accuracy of the target for the overall dissemination of information to the residents of the City of Tegal